Study of differences in motor reactions and performances in professional ice hockey players and not experienced participants using virtual reality (VR) technology - Polikanova, I.; Yakushina, A.; Leonov, S.; Yavorovskaya, A.; Kruchinina, A.; Chertopolokhov, V.; Liutsko, L. (Preprints, 2021)
The efficiency of performance in various sports has the development of certain specific skills at its core. In ice hockey, both the technical aspects (techniques, stance) and the cognitive ones (keeping attention on the puck, game strategy, etc.) are highly important. This study is aimed at the identification of specific features that determine the performance efficiency of professional hockey players. We used virtual reality (VR) to study the differences between professional ice hockey players and novices in terms of motor responses to the puck`s presentation on different levels of difficulty. The study involved 22 participants, 13 of them being professional ice hockey players (Mage=20±2.9; mean age of training experience ?=14.18±3.8) and 9 being not experienced participants (Mage=20±1.4). The study showed that the stick response time of professional hockey players is significantly higher (0.98 ms vs 1.5 ms, p=0.05) in more difficult situations close to a real game. Moreover, professionals proved to have more stable movement patterns of the knee and hip joints. They also make fewer head movements as a response to stimuli during all runs (0.66 vs 1.25, p=0.05). Therefore, the results indicate specific spatial-temporal, technical and tactical, and energetic determinants, that ensure higher performance efficiency in hockey players.